Initiation Of Smart Village Development In Lerep Tourism Village - Yuliani, Eppy; Karmilah, Mila (JACEE (Journal of Advanced Civil and Environmental Engineering), 2024)
Lerep Village, West Ungaran District, Semarang Regency is a tourist village that is widely known regionally and nationally.in the post-covid 19 pandemic era, the development of the Lerep tourism village has begun to rise. Along with the PPKM policy, this Tourism Village must be able to utilize information and communication technology (ICT) in order to be able to promote tourism objects to the wider community. The existence of the Smart Village concept is expected to be able to encourage the development of the Lerep Tourism Village, without eliminating local wisdom.Implementation of smart village through an approach that includes smart government, smart community, smart living, smart economy, smart environment, and smart mobility.The problem is the readiness and ability of the community and officials have not fully implemented the concept.The purpose of this research is to identify and analyze Smart Village initiatives in the management of the Lerep Tourism Village. The research was conducted in Lerep Village, West Ungaran District, Semarang Regency. with rationalistic qualitative deductive methods, descriptive analysis techniques. Conclusion Lerep Village already has an initiation of its smart village elements by not abandoning the local wisdom system at every village event. Keywords: initiation, smart, village, tourism